2019
DOI: 10.1152/jn.00812.2018
|View full text |Cite
|
Sign up to set email alerts
|

Angular vestibuloocular reflex responses in Otop1 mice. II. Otolith sensor input improves compensation after unilateral labyrinthectomy

Abstract: The role of the otoliths in mammals in the normal angular vestibuloocular reflex (VOR) was characterized in an accompanying study based on the Otopetrin1 (Otop1) mouse, which lacks functioning otoliths because of failure to develop otoconia but seems to have otherwise normal peripheral anatomy and neural circuitry. That study showed that otoliths do not contribute to the normal horizontal (rotation about Earth-vertical axis parallel to dorso-ventral axis) and vertical (rotation about Earth-vertical axis parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Our data is the first behavioral evidence to show correlations between improved DVA (putative semicircular canal function) and preserved otolith function (smaller magnitude asymmetry ratio) as measured by ocular and cervical VEMP. It has recently been shown that labyrinthectomized mice also missing otolith function (otopetrin 1), are unable to adapt their angular VOR gain as well as healthy mice (45). Our data support the murine evidence that otolith function does appear to have a critical role in compensation to semicircular canal damage.…”
Section: The Role Of Otolith Function On Compensation From Vestibularsupporting
confidence: 87%
“…Our data is the first behavioral evidence to show correlations between improved DVA (putative semicircular canal function) and preserved otolith function (smaller magnitude asymmetry ratio) as measured by ocular and cervical VEMP. It has recently been shown that labyrinthectomized mice also missing otolith function (otopetrin 1), are unable to adapt their angular VOR gain as well as healthy mice (45). Our data support the murine evidence that otolith function does appear to have a critical role in compensation to semicircular canal damage.…”
Section: The Role Of Otolith Function On Compensation From Vestibularsupporting
confidence: 87%
“…Although the otoliths do not encode angular acceleration themselves, they are known to be important in velocity storage (e.g., Angelaki et al, 1992; Koizuka et al, 1996; Mittelstaedt and Mittelstaedt, 1996; Wearne et al, 1999). Recent studies using Otop1 mice show that although the otoliths do not appear to contribute to the baseline angular velocity of the VOR in mice, they are necessary for its adaptation to changes in gravitational stimulation (Khan et al, 2019a, b). As Shinder and Taube (2014) noted, the fact that the otoliths are known to be important for HD cell firing, suggests that linear acceleration information from the otoliths and rotational acceleration information from the semi-circular canals, must converge by the time they reach the thalamus.…”
Section: Resultsmentioning
confidence: 99%
“…Het–/– mice exhibit a complete and specific loss of utricular and saccular otoconia (Bergstrom et al, 1998). Another model is the –/–; B6.Cg- Otop1tlt/j tilted mouse (Jackson Laboratories, Bar Harbor, ME; Jones et al, 2008; Kim et al, 2010), which exhibits a similar deletion of the otoliths (de Caprona et al, 2004; Blankenship et al, 2017; Khan et al, 2019a, b).…”
Section: Evidence For Otolithic Involvement In Spatial Memory In Micementioning
confidence: 99%
“…The crude product was purified by reverse phase HPLC (H 2 O/acetonitrile 10 to 90%) to afford the title compound 8 as a white solid (374.6 mg, 1.26 mmol, 60%). General Procedure B: N-(1-((3,5-Dimethylisoxazol-4-yl)methyl)-1H-pyrazol-4-yl)-3-hydroxybenzamide (19). The amine hydrochloride 6 (227 mg, 1.0 mmol), 3-hydroxybenzoic acid (138 mg, 1.0 mmol), PyBop (624 mg, 1.2 mmol), and triethylamine (0.28 mL, 2.0 mmol) were stirred in dimethylformamide (2 mL) at ambient temperature for 8 h under a nitrogen atmosphere.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…However, Horio et al later demonstrated that PKDs only contribute partly to the detection of sour taste in mice, thus pointing at the involvement of other receptors in sour taste mediation . More recently, the work by Tu et al identified otopetrin1 (OTOP1), a proton permeable protein that also plays a key role in the formation of gravity-sensing calcium carbonate crystals in the utricle of the ear, as being the sour taste receptor. ,, For salt taste perception in rodents, ENaC has been shown to participate, at least partially, but it does not seem to play a significant role in human salt taste perception . Other candidate salt receptors are still under evaluation.…”
Section: Introductionmentioning
confidence: 99%